Employ Successful Intelligence to Raise the Internal Auditor's Ability to Assess Risks: Evidence from Iraq - SAHIB, ABDULRASOOL ABDULABBAS; Wahhab, Asaad Mohammed Ali (Technium Business and Management, 2023)
The primary objective of the study is to assess the use of analytical intelligence, creative intelligence, and practical intelligence by internal auditors to improve their ability to assess risks and allocate work based on their unique capabilities and skills in accordance with the dimensions of successful intelligence represented by analytical intelligence, creative intelligence, and practical intelligence, and to assess the impact of these dimensions. As a result of the research's conclusion that successful intelligence has an apparent effect in terms of a positive relationship between it and the ability of internal auditors to assess risks, the research variables include the correlation between practical intelligence and the quality of work performed by internal audit departments. For the auditor and professional competence, the rate was (0.513), indicating the possibility of using the dimensions of the implicit theory to enhance the internal auditor's competence.